Ideology, patronage, and manipulation of translation in Zouxiang weilai congshu: With special reference to the translation and introduction of Max Weber - Cui, Feng (Frontiers in Communication, 2022)
Cultural Studies enables us to see that translation is not merely a simple and isolated process but is intricately bound to ideology, patronage, and poetics. Power relationships can be explored through the study of translated texts, which have the potential to reflect such power structures within a wider cultural context. This paper examines 走向未来丛书 (Zouxiang weilai congshu), literally ‘Toward the Future Book Series’, focusing on its selection and introduction of western texts and its interaction with Chinese ideological trends, to explore the relationship between translation and politics in the 1980s, focusing on discussing the translation and introduction of Max Weber.